KESULITAN GURU DALAM MENGEMBANGKAN PERANGKAT PEMBELAJARAN (MODUL AJAR) KURIKULUM MERDEKA DI SEKOLAH DASAR - Ceda, Katarina Aprillia; Purnomo, Heru (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
The aim of this research is to describe the problems or difficulties faced by teachers in developing learning instrumention in the merdeka curriculum. This research method uses qualitative research, a type of library research. The object of this research is the learning intrumentation in the merdeka curriculum developed by the teacher. The teaching module is a new language from the Lesson Plan (RPP) which has significant differences. The teaching module has three components, namely general information components, core components and attachments. Each component has further development, but the core components are the components of developing learning outcomes (CP), learning objectives (TP), learning objective flow (ATP) which become difficulties for teachers in developing teaching modules. In solving problems experienced by teachers when developing learning instrumentation, teachers must take part in any activities held regarding the merdeka curriculum, such as seminars, workshops, Teacher Working Groups (KKG), Subject Teachers' Conferences (MGMP), or look for information on books, articles , magazines, as well as the official website owned by the merdeka curriculum.